(untitled) (Research, Society and Development, 2022)
Obstetric Violence (VO) is “the appropriation of the woman’s body and her reproductive processes” during the assistance provided by health professionals. One of the main reasons for this scenario is the woman’s lack of information. This study aims to investigate the knowledge of nursing students about OV, understanding that they will be care professionals, responsible for providing guidance on the reproductive process, from prenatal care to puerperium, contributing to the expansion of knowledge and supporting the expansion of good practices in assistance to women. This is a quantitative and descriptive field study, carried out at a higher education college in Southwest Goiás, with (n=65) nursing students, from the first to the tenth period. An interview containing 12 objective questions was prepared, with a response time of 10-20 minutes. Data were analyzed using Microsoft Excel version 2019 (16.0), expressed as percentages and graphs. It was found that 86.2% of the participants are female, 62.1% aged between 18 and 23 years. Demonstrating that 84.4% have studied/and heard about obstetric violence, less frequently presenting knowledge about the imposition of the gynecological position during childbirth, 33.8% and regarding food restrictions and women’s mobility, 40.9%. It is concluded in this study that nursing students identified the main types of VO. In this way, this investigation demonstrated that the graduation of these professionals provides a scientific, critical and reflective basis related to women’s health.